EFEKTIVITAS PEMBELAJARAN PENDEKATAN OUT SIDE THE BOX DALAM MENYELESAIKAN MASALAH KREATIF MAHASISWA PENDIDIKAN MATEMATIKA - F.X. Didik Purwosetiyono; Achmad Buchori (LPPM Universitas Bina Bangsa, 2023)
This study examines the problem of learning effectiveness of the out side the box approach in solving creative problems in fifth semester mathematics education students at the University of Semarang in working on geometry problems. The sample technique used is cluster random sampling technique. The hypothesis test used is the one-sided test with the formula t test, completeness test, both tests are used to determine the effectiveness of learning. Based on the results of the study, the researchers draw the following conclusions; 1) Based on the results of this development research, it can be concluded that student learning outcomes in learning the out side the box approach in solving creative problems in mathematics education students in class VA are better than student learning outcomes in conventional learning class VB. 2) Based on the learning outcomes data for class students who use the out side the box learning approach in solving creative problems in mathematics education students seen from the percentage of completeness of learning outcomes achieving completeness